THE IMPACT EVALUATION OF THE INSTITUTIONAL REFORMS OF THE ONE-STOP SERVICE (OSS) ON ECONOMIC PERFORMANCE IN INDONESIA - Sakti Prabowo (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This paper examines the impacts of institutional reform of the One-Stop Service (OSS) structures on increases in Indonesia’s economic growth. This institutional reform aims to enhance the OSS effectiveness in developing a business regulatory simplification for a better business atmosphere, particularly for investments. According to Steer (2006), among three possible structures, which are units, offices, and departments, the most effective structure simplifying regulation is the department. Therefore, in 2016, there was a regulation in Indonesia, which set the obligation for local government at the district level to change the OSS structure into a department form. The impacts of reforms are then measured using staggered Difference-in-Difference (DID) methods. However, this paper finds that the reform may have significant negative effects on economic performance. There are some plausible underlying arguments to explain the findings. The impacts of institutional changes may have negative impacts in the short run due to the transition period of the reform. However, in the long run, such results may reverse. During this transition period, Indonesia may experience obstacles in implementing the reform. For example, human resources capacity is probably still low, and governance is poor. This, in turn, may hamper the effectiveness of the business regulation simplification. Also, the risk aversion behavior, which may impede entrepreneurship, may still dominate Indonesian people and thus hamper the effectiveness of institutional reforms. Therefore, this can impede the effectiveness of reform on the economic performance in Indonesia.